Technology Choice and Technology Transfer - Neelameghan, A. (Journal of Information and Knowledge, 1977)
Presents the five aspects of technology planning and management. Discusses the activity components and information needs of technology planning and management. The constraints on technology diffusion, factors affecting communication of knowledge, attributes of communicator and communicatee and the barriers of communication, are discussed. Cognisance of socio-economic and political factors in technology choice and technology transfer is emphasized.